The Macroeconomic Implications of Ageing in a Global Context - Turner, Dave (OECD Economics Department Working Papers, 1998)
This study was prepared in the Economics Department as a contribution to the Organisation -wide study of the economic consequences of population ageing. It presents a number of long-term scenarios illustrating the likely domestic and international macroeconomic effects of ageing across the OECD and policies which might ameliorate or reverse underlying tensions. This work draws together the broad range of elements involved within a consistent framework, based on the Secretariat's new international dynamic general equilibrium macroeconomic model (MINILINK). A "business-as-usual" case is examined in which, without improvements in labour market performance or specific policy adjustments to allow for the pressures of ageing, economic growth is projected to slow significantly over the next 50 years in nearly all OECD countries; world real interest rates remain stable at current levels or even rise, because of the effects of ageing on private savings and the possible build-up of public ...